Positive Energy District: A Model for Historic Districts to Address Energy Poverty - Gouveia, João Pedro; Seixas, Júlia; Palma, Pedro; Duarte, Henrique; Luz, Henrique; Cavadini, Giovan Battista (Frontiers in Sustainable Cities, 2021)
The Positive Energy District (PED) concept has been pointed out as key for cities' energy system transformation toward carbon neutrality. The PED may be defined as an energy-efficient and flexible urban area with net-zero energy import and greenhouse gas emissions, aiming toward annual local surplus of renewable energy. Most of the studies and practical experiences about PEDs are based on newly built districts, where the planning and integration of innovative solutions are less complex and more cost-effective. However, to achieve Europe Union's 2050 carbon-neutral ambition, we argue that the transformation of the settled districts is essential, including historic districts, which present common challenges across European cities, such as degraded dwellings, low-income families, and gentrification processes due to massive tourism flows. This paper aims to discuss how the PED model can be an opportunity for historic districts to reduce their emissions and mitigate energy poverty. The historic district of Alfama, in the city of Lisbon (Portugal), is used as a case study to show the potential of energy renovation measures and solar PV production in households, cornerstones of a PED. The annual energy needs potential reduction due to building retrofit is 84 and 19% for space heating and cooling, respectively, while the integration of building-integrated PV technologies in rooftops and windows potentially generates up to 60 GWh/year. At the district scale, these two components of the PED concept could require an investment of 60M€ to 81M€ depending on the PV technologies in the rooftops, a sensitive aspect in historical districts. Unlike other mechanisms to tackle energy poverty, like the social tariffs, the adoption of structural measures like building energy efficiency retrofit and renewable energy integration will contribute to solve the energy poverty problem, which is significant in Alfama, in both the winter and summer. The highlighted investments require an innovative financial scheme to support not only buildings' owners but also tenants, as these are among the most vulnerable to energy poverty. However, the social benefits of that investment, on the health system, air quality, climate resilience, labor productivity, and social integration, would be invaluable.